A study on the vinyl acetate-co-butyl acrylate latexes in the presence of n-methylol acrylamide and mixed type emulsifiers - Kahraman, Ayca; Sarac, Ayfer (WILEY-V C H VERLAG GMBH, 2007)
The properties of copolymer latexes depend on the copolymer composition, polymer morphology, initiator, polymerization medium and colloidal characteristics of copolymer particles. Poly(vinyl acetate-co-butyl acrylate) latexes with N-metylol acrylamide were prepared by applying semicontinuous emulsion polymerization. The systems studied were (a) the mixture of anionic sodium lauryl sulfate ether (SELES) with nonionic 30 moles ethoxylated nonyl phenol (NP 30) (50:50), (b) the mixture of anionic sodium lauryl sulfate ether (SELES) with nonionic 30 moles ethoxylated nonyl phenol (NP 30) (70:30), and (c) anionic sodium lauryl sulfate ether (SELES) (100%). The effects of the emulsifier and emulsifier composition on the physicochemical properties of obtained vinyl acetate-co-butyl acrylate latex properties in the presence of N-methylol acrylamide initiated by ammonium persulfate were investigated.
Keywords: emulsion polymerization; lattices; stabilization; surfactants; EMULSION COPOLYMERIZATION; POLYMERIZATION; Polymer Science